Pengaruh Penggunaan Balon sebagai Alat Peraga pada Pembelajaran Materi Bentuk Molekul Terhadap Hasil Belajar dan Aktivitas Siswa Kelas X MIPA 1 di SMA Negeri 3 Kotabumi Tahun Pelajaran 2018--2019 - Siti Mursida (Eksponen, 2020)
The purpose of this study was to improve the learning outcomes of students in X MIPA 1 SMAN 3 Kotabumi for the 2018-2019 academic year by using balloons as a medium for learning material in molecular form.This research was designed in the form of classroom action research and was carried out in class x mipa 1 students of SMAN 3 Kotabumi in the 2018-2019 academic year. The research consisted of 2 cycles in the first cycle about VSEPR theory and the second cycle about hybridization theory. In the implementation of the research, the use of balloon media was tested in studying the molecular shape material, then analyzed whether there was an effect on student learning outcomes. Data collection techniques using cognitive tests and student attitude questionnaires obtained from each cycle, the results were analyzed whether there was an increase in each cycle. Based on the results of this study, it shows that the use of balloons as teaching aids in learning material in molecular form can help improve learning outcomes of chemistry and student activities in class X MIPA 1. There is an increase in learning outcomes by 33% from cycle I to cycle II, while student activities based on questionnaires have increased in cycle II where students, easier to remember, easier to understand, happy with learning chemistry and active in learning. The conclusion of this study is that the use of balloons as teaching aids in learning material in molecular form can help improve learning outcomes of class X MIPA 1 students at SMAN 3 Kotabumi in the 2018-2019 academic year.